Badanie elastyczności przedsiębiorstw - Krupski, Rafał (Research of enterprise flexibility, 2005)
The article presents the examples of enterprise flexibility research based on the literaturę dealing with this subject. The author presented his own method of flexibility research and introductory research conclusions of 180 enterprises. These conclusions were presented in following profiles: the enterprise size (measured by the number of employees), the enterprise global flexibility and factors creating this flexibility.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 145-152